Psilocybin-assisted psychotherapy for methamphetamine dependence: a case report involving daily methamphetamine use - Brett, Jonathan; Knock, Elizabeth; Watson, Kathy; Albert, Steven; Siefried, Krista J.; Guss, Jeffrey (Frontiers in Psychiatry, 2024)
Methamphetamine (MA) dependence leads to severe physical and psychological issues. Current treatments, including psychosocial therapies and residential rehabilitation, face limitations such as high relapse rates, cost, and accessibility issues. As a result, there is an urgent need for novel approaches to treat MA dependence that are effective, affordable, and accessible to patients. Psilocybin, the active component in numerous mushrooms of the Psilocybe genus, has shown potential for enhancing psychotherapy for various addiction and mental health issues due to its effects on perception, cognition, and affect. Psilocybin-assisted psychotherapy (PAT) has demonstrated initial safety and efficacy in treating alcohol, cocaine, and nicotine dependence. The case presented here describes a 36-year-old transwoman and daily MA user, who participated in a single-arm open-label clinical trial assessing feasibility and safety of PAT for MA dependence at St. Vincent’s Hospital, Sydney. Following inpatient withdrawal management and one session of psilocybin-assisted therapy, she experienced significant cognitive and emotional shifts and sustained MA abstinence. She reported improved mental health over 3 months following treatment completion. She also noted increased self-esteem, mindfulness, and distress tolerance. This study suggests that PAT (following inpatient MA withdrawal management) may offer a scalable, safe, and effective approach for treating MA dependence. However, further research is required to confirm the generalisability and efficacy of PAT for broader populations of people using MA. It is encouraging that this participant, a daily MA user, showed improvements in mood and cognition, in addition to abstinence from MA.